2015
DOI: 10.1016/j.bjid.2014.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Clinical relevance of rhinovirus infections among adult hospitalized patients

Abstract: Human rhinovirus infections in elderly patients with co-morbid conditions are associated with hospitalizations, requiring critical or semi-critical antibiotics use. A high CURB-65 score was associated to in-hospital mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
19
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 38 publications
(74 reference statements)
5
19
1
3
Order By: Relevance
“…Previous studies have reported that the HRV infection rate in hospitals varies from 21% to 41%. 8,11,12 However, this variation is probably accounted for by the differences in age and clinical characteristics of patients analyzed in each study. Although this study included all age groups, a predominance of pediatric patients infected with HRV was observed, mostly younger than 1 year old.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that the HRV infection rate in hospitals varies from 21% to 41%. 8,11,12 However, this variation is probably accounted for by the differences in age and clinical characteristics of patients analyzed in each study. Although this study included all age groups, a predominance of pediatric patients infected with HRV was observed, mostly younger than 1 year old.…”
Section: Discussionmentioning
confidence: 99%
“…Estudos anteriores relataram que a taxa de infecção por RVH em hospitais varia de 21%-41%. 8,11,12 Contudo, essa variação é provavelmente explicada pelas diferenças na idade e nas características clínicas dos pacientes analisados em cada estudo. Apesar de este estudo ter incluído todas as faixas etárias, observamos uma predominância de pacientes pediátricos infectados por RVH, em grande parte pacientes com menos de um ano.…”
Section: Discussionunclassified
“…19,20 Os achados de raios X de tórax foram normais em 17%, mostraram infiltrado intersticial em 33% e consolidação pulmonar em 28% dos casos, sem diferença significativa entre os grupos RVH e outros VRCs. Esses padrões são semelhantes aos relatados por Fica et al 11 em adultos internados no Chile. Houve um número significativamente menor de casos de SARI diagnosticado nos pacientes infectados por RVH do que outros VRCs.…”
Section: Discussionunclassified
“…Thus, the proportion of RV may be different in the general population seeking medical care. A few other studies have reported the proportion of adults with RVassociated ARI to be from 4% to 23%; however, these examined specimens that had tested negative for other viruses, 51 had small sample sizes, 52 or selected for subjects presenting with fever, 34,53 thus likely underestimating the prevalence of RV. The rates of RVassociated hospitalization we detected were generally lower than those reported in a similarly designed study of young children in this same geographic region (5 per 1000/y overall for children aged 0-5 years).…”
Section: Discussionmentioning
confidence: 99%
“…14,16,17,20,[26][27][28][29][30][31] The recently described RV-C has been associated with wheezing and more severe respiratory symptoms in children, 32,33 but these findings have been inconsistent and data are limited in adults. 34,35 The impact of the novel RV-C on US adults has not been established, and the association of RV-C with asthma and COPD is unclear.…”
mentioning
confidence: 99%